Analisis Pengawasan Pajak Air Tanah Untuk Meningkatkan Pendapatan Asli Daerah Di Badan Pendapatan Daerah Provinsi DKI Jakarta Tahun 2018 – 2020 - Siti Julaiha; Aiat Sudraiat (Jurnal Ilmu Administrasi Publik, 2023)
The purpose of this research is to analyze how to monitor the land water tax in the District Revenue Agency of the Province of Jakarta, to analyze the obstacles experienced by the fiscal authorities against taxpayers who avoid land water tax, and to analyze supporting factors that can optimize the monitoring of land water. This research uses a qualitative approach with observation techniques and in-depth interviews with the Head of the Executive Unit of the Data and Revenue Information Center of the DKI Jakarta Provincial Income Agency, academics, and taxpayers. The results of this study concluded that groundwater tax supervision has been sufficient. The problems that are faced are in the unit of tax recovery service in the area where the amount of SDM is minimal, while the number of tax obligations in one area of UPPPD is many. Another obstacle is the condition of the COVID-19 pandemic, where the activities of the community are limited and do not allow for the fiscal services to be performed directly. Efforts undertaken in the face of barriers in the Land and Water Tax Surveillance in the District Revenue Agency of DKI Jakarta should continue to perform optimal surveillance under any circumstances, as well as transform all types of regional taxes digitally or through the website. Recommendations for the Regional Revenue Agency of DKI Jakarta to promptly increase the amount of taxation (human resources), as well as monitoring to improve compliance, should be held. Socialization and special attention related to taxpayers who have not yet understood taxation are needed to increase taxpayer awareness and help them fulfill their tax obligations.